Effect of the Delay Between the Detection of Vibration and the Action of Tendons on the Dynamics Response of Tension Leg Platform (TLP) Under Sea Waves Excitation - Ngounou, A.M.; Nbendjo, B.R. Nana; Dorka, U. (Journal of Applied Nonlinear Dynamics, 2026)
In this study, the dynamic response of the tension leg platform (TLP) under sea waves excitation is investigated. One establishes the analytical framework consisting of mathematical modeling of TLP taking into account the tendons and the delay. We analyse the stability and determine the physical characteristics of tendon system that allow the system to be always stable. Conditions on the space parameters of the system for which harmonic, subharmonic, superharmonic, combination resonants states are obtained using the multiple time scales method. The results show that the stability area of the system decreases when the delay increases and increases when the damping coefficient increases. Furthermore, increasing the time- delay only increases the value of the maximum amplitude response of the system. However, reasonable selection of the system parameters can effectively reduce the level of vibration of the system.